Mycorrhizal Preferences And Fine Spatial Structure Of The Epiphytic Orchid Epidendrum Rhopalostele - Cruz Sarmiento, D. (2013)
Premise of the study: The presence of compatible fungi is necessary for epiphytic orchid recruitment. Thus, identifying associated mycorrhizal fungi at the population level is essential for orchid conservation. Recruitment patterns may also be conditioned by factors such as seed dispersal range and specific environmental characteristics. Methods: In a forest plot, all trees with a diameter at breast height > 1 cm and all individuals of the epiphytic orchid Epidendrum rhopalostele were identified and mapped. Additionally, one flowering individual of E. rhopalostele per each host tree was randomly selected for root sampling and DNA extraction. Key results: A total of 239 E. rhopalostele individuals were located in 25 of the 714 potential host trees. Light microscopy of sampled roots showed mycorrhizal fungi in 22 of the 25 sampled orchids. Phylogenetic analysis of ITS1-5.8S-ITS2 sequences yielded two Tulasnella clades. In four cases, plants were found to be associated with both clades. The difference between univariate and bivariate K functions was consistent with the random labeling null model at all spatial scales, indicating that trees hosting clades A and B of Tulasnella are not spatially segregated. The analysis of the inhomogenous K function showed that host trees are not clustered, suggesting no limitations to population-scale dispersal. chi(2) analysis of contingency tables showed that E. rhopalostele is more frequent on dead trees than expected. Conclusions: Epidendrum rhopalostele establishes mycorrhizal associations with at least two different Tulasnella species. The analysis of the distribution patterns of this orchid suggests a microsite preference for dead trees and no seed dispersal limitation.